Angiopoietin II in Critically Ill Septic Patients: A Post Hoc Analysis of the DRAK Study - Veronika Bucher; Helen Graf; Johannes Zander; Uwe Liebchen; Danilo Hackner; Caroline Gräfe; Martin Bender; Michael Zoller; Christina Scharf (Biomedicines, 2024)
Introduction: Angiopoietin II (Ang-II) plays a pivotal role in the development of microcirculatory dysfunction as it provokes endothelial barrier disruption in patients with sepsis or septic shock. In particular, those with acute kidney injury show high Ang-II concentrations. So far, it is unclear which covariates influence Ang-II concentration in the early phase of sepsis, especially if extracorporeal therapies also do. Methods: Ang-II concentrations were measured in 171 patients with sepsis after the first day of antibiotic treatment between 03/2013 and 01/2015. Ang-II was correlated with potential influencing factors (Spearman correlation). A multivariate model was established including the significant correlating parameters. The Mann–Whitney U test and the Kruskal–Wallis test were used to detect significant differences in Ang-II concentration. Results: The median Ang-II concentration was 8015 pg/mL (interquartile range (IQR): 5024–14,185). A total of forty patients were treated with kidney replacement therapy (KRT) and 20 were supported by venovenous extracorporeal membrane oxygenation (vv-ECMO). Sequential organ failure assessment (SOFA) score (r = 0.541), creatinine clearance (r = −0.467), urinary output (r = −0.289), interleukin (IL)-6 (r = 0.529), C-reactive protein (CRP) (r = 0.241), platelet count (r = −0.419), bilirubin (r = 0.565), lactate (r = 0.322), KRT (r = 0.451), and fluid balance (r = 0.373) significantly correlated with Ang-II concentration and were included in the multivariate model. There, creatinine clearance (p < 0.01, b = −26.3, 95% confidence interval (CI) −41.8–−10.8), fluid balance (p = 0.002, b = 0.92, 95% CI 0.33–1.51), and CRP (p = 0.004, b = 127.6, 95% CI 41.6–213.7) were associated with Ang-II concentration. Furthermore, patients with KRT (median: 15,219 pg/mL, IQR: 10,548–20,270) had significantly (p < 0.01) higher Ang-II concentrations than those with vv-ECMO support (median: 6412 pg/mL, IQR: 5246–10,257) or those without extracorporeal therapy (median: 7156 pg/mL, IQR: 4409–12,741). Conclusion: Increased CRP, positive fluid balance, and impaired kidney function were associated with higher Ang-II concentrations in critically ill patients in the early stage of sepsis in this post hoc analysis. In particular, patients with KRT had very high Ang-II concentrations, whereas the use of vv-ECMO was not related to higher Ang-II concentrations. The significance for clinical practice should be clarified by a prospective study with standardized measurements.